Quantitative imaging for 177Lu-PSMA treatment response monitoring and dosimetry - Meyer, Catherine; Szidonya, Laszlo; Winters, Celeste; Mench, Anna; Mallak, Nadine; Mittra, Erik (Frontiers in Nuclear Medicine, 2023)
PSMA-targeted radiopharmaceutical therapy is an established treatment option for metastatic castration-resistant prostate cancer (mCRPC). However, response rates and duration using 177Lu-PSMA-617 vary considerably between patients. Quantitative 177Lu SPECT imaging is one approach that may be leveraged to more closely monitor inter-cycle response, as well as patient-specific absorbed doses. In this work, we describe our experience implementing quantitative imaging throughout the course of 177Lu-PSMA treatment, including serial SPECT imaging to monitor response and for individualized dosimetry. We also describe our imaging protocols and dose calculation workflows for 3D voxelized patient-specific organ and tumor dosimetry, including a review of the current landscape and efforts towards harmonized dosimetry.